Combined functions of two RRMs in dead-end1 mimic helicase activity to promote nanos1 translation in the germline - Agüero, Tristán Horacio (2018)
Dead-end1 expression is restricted to the vertebrate germline where it is believed to activate translation of mRNAs required to protect and promote that unique lineage. nanos1 is one such germline mRNA whose translation is blocked by a secondary mRNA structure within the ORF. Dead-end1 contains a canonical mRNA Recognition Motif (RRM1) in its N-terminus but also contains a less conserved RRM2. Here we provide a mechanistic picture of the nanos1 mRNA-Dead-end1 interaction in the Xenopus germline. We show that RRM1, but not RRM2, is required for binding nanos1. Similar to the zebrafish homologue, Xenopus Dead-end1 possesses ATPase activity. Surprisingly, this activity appears to be within the RRM2, different from the C-terminal region where it is found in zebrafish. More importantly, we show that RRM2 is required for nanos1 translation and germline survival. Further, Dead-end1 functions as a homodimer and binds nanos1 mRNA just downstream of the secondary structure required for nanos1 repression. We propose a model in which the RRM1 is required to bind nanos1 mRNA while the RRM2 is required to promote translation through the action of ATPase. Dead-end1 appears to use RRMs to mimic the function of helicases.